Perfiles de disolución de tres tipos de tabletas que contienen 10 mg de Ketorolaco Trometamina comercializados en Lima - Perú - Aroca Sevillano, Eduard Diego Alonso (2017)
The present work aims to evaluate the dissolution profiles of three types of tablets containing 10 mg of ketorolac tromethamine marketed in Lima, Peru. The tests were carried out in the Agilent team 708-DS, using as the medium of dissolution 600 mL of water, type of apparatus 2, the agitation speed of 50 turns for 45 minutes, as described in United State Pharmacopeia 38. In addition to the dissolution profile graphs. The dissolution efficiency (ED) parameters were calculated. According to the analysis results of the evaluated formulations A, B, C, can be concluded that they accomplish the pharmacopoeial specifications, releasing a percentage equal to 75% for less than 45 minutes. Finally, it can be concluded that the dissolution profiles of three types of tablets evaluated are equivalent